Embracing Greek philosophical thinking in the fathers of the 2nd - 5th centuries - Artemi, Eirini (Vox Patrum, 2016)
Christianity adopted Greek language and thought it existed within a Greek cultural milieu and Hellenic historical setting. As a whole, however, the Fathers of the Greek Church did not seek to borrow either the essence or content from ancient Greek thought, for those they possessed in their sacred Scriptures. The Church Fathers put together the best parts of Greek classical antiquity with the best of the teaching of Christian theology. Nevertheless, in this effort Christian revelation did not escape infiltration by Greek thought, and Greek cultural and intellectual influences became interwoven with Christian faith. It was Christianity’s encounter with Hellenism that made the former a cosmopolitan religion. This relationship, not without periodic tensions, prevailed throughout the Byzantine millennium and centuries beyond. Long before modern anthropologists, philosophers, and theologians, these Church fathers confirmed that Greek culture is the outer garment of religion and religion is the heart of culture, and that the two are inseparable. In this manner, the Hellenic heritage of literal texts can be considered a part of our Church’s heritage. Christianity embraced Greek classical heritage while rejecting pagan cults.